Teologi Misi, Pendidikan Perdamaian dan Keadilan Umat Beragama di Indonesia dalam Perspektif Alkitab dan Pengamalan Kristiani - Hesra Sembiring; Elia Tambunan (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2026)
The life of Christians who are Indonesians in the reality of religious people is unique. For Christians, there is a social understanding of the importance of peace in public life contained in the Bible is no longer limited to religious books but also social life books that validate religious people to influence social structures. Understanding is born from social relations that are realized and then constructed because reading the Bible is the Word of God that is accepted, recognized and used in a religious society as something sacred and authoritative. The content is a life lesson that initiates various forms of social affirmative action. The theoretical concept that underlies this paper we build on Christian theaching. This is a descriptive qualitative research with a literature study by a critical reading of many cited literatures and digital ethnography. The goal is to build an academic framework that is useful as analitical instrument to conduct field research that can be used and continued to be developed by other academics. It was found that even the essence of peace, justice is difficult to realize, but the Bible can be a common value for humans. The novelty offered in this paper is that the theology, mission, and education of Shalom Christianity in a plural and multicultural religious community is based on the use of religious books as teachings for each individual and society, not only understood as a discourse on conflict justification, but also lived every day. Abstrak Hidup orang Kristen yang adalah orang Indonesia dalam kenyataan umat beragama ialah unik. Bagi Kristen ada keinsyafan sosial betapa pentingnya perdamaian dalam kehidupan publik yang termuat pada Alkitab bukan lagi sebatas kitab keagamaan namun juga kitab kehidupan sosial yang memvalidasi umat beragama untuk mempengaruhi struktur sosial. Keinsyafaran lahir dari relasi sosial yang tersadari lalu terbangun karena membaca Alkitab adalah Firman Allah yang diterima, diakui dan digunakan dalam suatu masyarakat beragama sebagai sesuatu yang suci sekaligus berwibawa. Isinya adalah ajaran kehidupan yang menginisiasi berbagai corak tindakan afirmatif sosial. Konsep teoritis yang melandasi tulisan ini kami bangun berdasarkan ajaran Kristen. Ini adalah penelitian kualitatif deskriptif dengan studi kepustakaan namun disertai pembacaan kritis terhadap banyak literatur yang dicitasi dan etnografi digital. Tujuannya ialah membangun kerangka kerja akademis yang berguna sebagai instrumen analisis ketika melakukan penelitian lapangan yang dapat dipakai dan terus dikembangkan oleh akademisi lainnya. Ditemukan bahwa esensi perdamaian, keadilan sekalipun sulit mewujudkannya, namun Alkitab dapat menjadi common values bagi manusia. Kebaruan ditawarkan dalam tulisan ini adalah teologi misi dan pendidikan Shalom Kristen dalam umat beragama yang plural dan multikultural didaraskan dari penggunaan kitab keagamaan sebagai ajaran bagi tiap-tiap individu maupun sosial tidak dipahami sebatas wacana justifikasi konflik tetapi juga terhidupi setiap hari.